Longing for evidence-based traditions: Addiction treatment in Canada's Northwest Territories (Medicine Anthropology Theory, 2020)
In Native North America, clinical/healing spaces are caught up in political struggles for autonomy. In Canada’s Northwest Territories, where rates of alcohol consumption are substantially higher than national averages, there are ongoing attempts to align therapeutic practice with traditional Aboriginal modes of healing and well-being. This Think Piece traces the ‘therapeutic trajectory’ of alcohol treatment in and out of this subarctic region. I show how the language of ‘evidence-based practice’ affords both gains and losses with regard to the assertion of collective identity and values vis-à-vis the state. Against the backdrop of the closure of the region’s sole residential treatment program, I contrast a conversation with a clinician responsible for implementing culture-based programs with the experiences of Destiny, a young Dene woman who, in the absence of local treatment options, spends time in clinics some one thousand kilometers away from her home community. In her movements away from the place to which she is indigenous, Destiny activates different forms of Aboriginal care than those intended by state and community actors. These divergent perspectives speak to the enmeshment of addiction with the perils and politics of liberal forms of recognition.